Kill the king : a novel - Dazieri, Sandrone, 1964- (Dazieri, Sandrone, 1964- Caselli and Torre series, 2020)
From thriller master Sandrone Dazieri, here is the startling conclusion to the internationally bestselling Caselli and Torre trilogy in which two damaged but deductively brilliant detectives must sort out what is real and what is imagined. Reeling from a deadly bombing in Venice and her investigative partner Dante's disappearance, Detective Colomba Caselli retreats to the rural countryside outside Rome to nurse her wounds. When an apparently autistic teenager appears in her yard, covered in blood, he leads her to a brutal crime scene where nothing is what it seems. As Colomba gets pulled into the investigation and the body count spirals upward, she is implicated in the violence. Soon, she's convinced that a powerful villain is working in the shadows to cause the carnage and frame her, but the only person who can help her is Dante--and he hasn't been seen in over a year and is presumed dead. Colomba is sure he's alive and out there somewhere, but will she find him before it's too late? And can she clear her name and be free of the far-reaching legacy of the villain known as the Father?